The Economical Analysis of Cattle Manure Treatment by Anaerobic Digestion Process - Coskun, Tamer; Demir, Neslihan Manav; Debik, Eyup; Karadag, Yasar; Kocyigit, Rasim; Ozkurt, Mahir; Akbay, Seda (KARABUK UNIV, 2012)
Cattle manure is a potential for causing detrimental effects on human health due to its high solid matter and pathogen microorganism content. This study aims to achieve biogas production by stabilizing the waste using anaerobic digestion. Digested waste was utilized as natural fertilizer. For that reason, a pilot-scale anaerobic digestion tank was operated and digested wastes were added to soil in diverse dosages where alfalfa, the mixture of Hungarian vetch and barley and corn silage are planted. Corn silage was fed to the reactor as a supplementary material during anaerobic digestion process. Installation and operating costs are determined for 1,000 cattle by the results obtained and the literature datas. Installation cost was evaluated considering both installed electricity producted system and non-installed electricity producted system. As a result, according to best results, the system would pay for itself in 2. 5 years when electricity production system is installed while the system is not installed, the payoff would be realized in 2. 1 years for the mixture of Hungarian vetch and barley.
Keywords: Biogas; cattle manure; payback period; anaerobic digestion; Arts & Humanities - Other Topics